Adverse childhood experiences, safeguarding and the role of the school nurse in promoting resilience and wellbeing. (2nd February 2022) - Waterhouse, Judith Anna
Abstract : Background: School nurses are key professionals in helping to safeguard, support and improve outcomes for children and young people. Aim: The aim of this article is to explore the subject of adverse childhood experiences (ACEs) in relation to safeguarding and the vital role the school nurse can play in supporting the building of resilience in children and young people (CYP) and their families. Methods: A critical review of the literature was undertaken, considering the role of the school nurse within the safeguarding arena, adverse childhood experiences, collaborative and multi-agency work. The legal, policy and professional frameworks underpinning safeguarding and public health practice are also critically examined. Findings: There is ample evidence demonstrating the potential effects of ACEs on the health and wellbeing of children and young people. There is also research proposing that ACEs should not be viewed in isolation and are not necessarily in themselves deterministic of negative outcomes. School nurses have an important role in early interventions with families to promote resilience and help keep children safe. Conclusion: The implication of this article is that with sound knowledge and understanding regarding ACEs, the school nurse can play a vital role as part of the wider team in building the resilience of the community, provide therapeutic interventions and early intervention, and thereby help to safeguard, support, and improve outcomes for CYP and their families.